Análise da influência dos parâmetros de soldagem na microestrutura e propriedades mecânicas de uma junta soldada de tubos sem costura API X70QS para aplicações Linepipe Sour Service - Mariana Pessoa Medeiros (2018)
The steel grade X70 is a material that presents a good relationship between mechanical strength and toughness, being increasingly used in oil & gas transportation. Among the many benefits of using this material for this application, the major one is the decreasing in line weight, because, by increasing the yield strength of a material, the wall thickness required to support internal or external pressures may be reduced with the consequent reduction of the amount of material to be used. This implies in a good cost / benefit ratio in the application and installation of pipelines. With the objective to evaluate the weldability of API 5L X70QS seamless steel pipes, microstructural and mechanical characteristics of joints obtained by GTAW (root) and GMAW (filling) processes were evaluated along their cross section. Tube segments were machined in J-bevel shape. Circumferential welding was performed rotating the pipe in order to maintain flat welding position. In this study three different heat inputs were applied. Specimens for tensile, Vickers hardness, charpy impact, chemical analysis, corrosion and metallographic characterization tests were cut from the base material and from the welded joints. The grade X70QS obtained and welded with different heat inputs showed adequate mechanical behavior and corrosion resistance in applications in sour service environment